(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2015)
This paper discusses the lyrics in the patriotic songs of the Malay-Muslim community in Pattani. This study examines the lyrics of patriotic songs that have spread through internet. The lyrics of these patriotic songs evoke the spirit of the Muslim Pattani Malay community, whether living in Pattani or whether they have migrated to foreign lands. The diction in these lyrics sung by a handful of artists from Pattani, and disseminated through new media tools such as youtube, facebook and blogs to make their voices heard to the people all around the world, aims to incite their fighting spirit. For this study, Max Weber’s theory of authority or power, which includes aspects of authority, the use of violence as a weapon, and charisma, was applied. The research concludes that the song lyrics incite the Pattani Malay-Muslim community to continue to fight for the independence of their homeland, people, language and religion in the politically volatile area of southern Thailand. Keywords: Pattani, authority, patriotic song lyrics, new media, freedom fighter-colonizer narrative